2019
DOI: 10.1002/aoc.4765
|View full text |Cite
|
Sign up to set email alerts
|

The functionality of the hybrid systems driven by molecular dimension of the guest copper Schiff‐base complexes entrapped in Zeolite‐Y

Abstract: On encapsulation inside the supercage of zeolite‐Y planar Cu (II)–Schiff base complexes show the modified structural, optical and functional properties. The electronic effect of the different substituent groups present in the catalyst plays the decisive role towards their reactivity in the homogeneous phase but after the encapsulation in zeolite Y, reactivity is mainly governed by the molecular dimensions of the guest complexes rather than the electronic factor of the substituent groups attached on them. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The binding energies of Cu (2p 3/2 ) and Cu (2p 1/2 ) validate that the copper metals are in a +2 oxidation state in all complexes. 35 The XPS signals of Cu are present at 933.93 eV (Cu2p 1/2 ) and 953.94 eV (Cu2p 3/2 ) for L 1 Cu(OAc). However, for L 1 Cu(OAc)-Y, L 2 Cu(OAc)-Y, and L 3 Cu(OAc)-Y, the signal peaks are observed at 935.09, 955.07, 935.68, 955.63, 935.16, and 955.07 eV, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The binding energies of Cu (2p 3/2 ) and Cu (2p 1/2 ) validate that the copper metals are in a +2 oxidation state in all complexes. 35 The XPS signals of Cu are present at 933.93 eV (Cu2p 1/2 ) and 953.94 eV (Cu2p 3/2 ) for L 1 Cu(OAc). However, for L 1 Cu(OAc)-Y, L 2 Cu(OAc)-Y, and L 3 Cu(OAc)-Y, the signal peaks are observed at 935.09, 955.07, 935.68, 955.63, 935.16, and 955.07 eV, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The order of catalytic performance for encapsulated complexes is as follows: L 3 Cu(OAc)-Y > L 1 Cu(OAc)-Y > L 2 Cu(OAc)-Y. 34,35 Moreover, there was an obvious blueshift of the d-d transition in the UV-Vis spectrum as compared with free complexes, and the order of the blueshift is: L 3 Cu(OAc)-Y > L 1 Cu (OAc)-Y > L 2 Cu(OAc)-Y. For L 2 Cu(OAc)-Y, the shift is less than that of L 1 Cu(OAc)-Y and L 3 Cu(OAc)-Y.…”
Section: Structural and Functional Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their structural properties, biocompatibility, and stability in biological environments, these porous materials have numerous applications in biology as an active ingredient as well as a drug carrier. It is observed that when both the zeolite and a drug are administered simultaneously to a patient, the pharmacological effect of the drug is not lost. It has been shown that the encapsulation of some hydrophobic chemotherapeutic medicines such as 5-fluorouracil, temozolomide, and α-cyano-4-hydroxy-cinnamic acid in various zeolite structures enhanced the action of drug molecules in biological system. ,, Even the internalization of various zeolite moieties within cancer cells was found to be faster than the normal cell lines. Encapsulation of different transition-metal complexes with molecular dimensions comparable to the diameter of zeolitic cavities has been immensely endeavored and numerous applications have been accentuated. A copper Schiff base complex encapsulated inside zeolite-Y was screened for its cytotoxic activity. Interestingly, in comparison to cisplatin, a zeolite-Y-encapsulated Cu­(II)­hydrazone complex has shown a superior therapeutic effect in HePG2 cells (human liver cancer).…”
Section: Introductionmentioning
confidence: 99%